Pemetaan Materi Ajar Ekonomi Jenjang SMA/MA Berdasarkan Kurikulum Merdeka - Saputra, Maskhur Dwi; Bahrudin (Arus Jurnal Pendidikan, 2024)
This study aims to map the teaching materials for Economics at the SMA / MA level according to the Merdeka Curriculum. This type of research uses a qualitative descriptive approach with a literature study research method. The research data used is secondary data by listing the Learning Outcomes of Economics subjects at the SMA / MA level according to the decision of the National Standards, Curriculum and Assessment Agency Number 033 / H / KR / 2022. Then from the Learning Outcomes it is mapped into more specific Economics teaching materials. The data analysis technique consists of three stages, namely (1) data reduction; (2) data display; (3) conclusion drawing. The results showed that the Learning Outcomes at the SMA/MA level are divided into two phases, namely phase E and D, where phase E is for class X while phase F is for classes XI and XII. The mapping of phase E teaching materials are (1) scarcity and opportunity cost; (2) priority scale; (3) economic system; (4) market balance; (5) payment system and money; (6) non-cash payment instruments; and (7) bank and non-bank financial institutions. The mapping of phase F teaching materials is (1) business entities; (2) basic financial accounting; (3) national income; (4) economic growth and development; (5) employment and unemployment; (6) money theory, price index, and inflation; (7) money market and digital economy; (8) monetary and fiscal policy; (9) taxation; and (10) international economy. Based on these two phases, learners are encouraged to master the skills of microeconomics, macroeconomics, monetary economics, international economics, accounting science, and management.